Frequency tuning varactor-loaded reconfigurable antenna for m-WiMAX and WLAN applications - Shah, S. M.; Hamdan, K.; Z. Abidin, Z.; C. Seman, F.; Hamzah, S. A.; Katiran, N.; Zubir, F. (Institute of Advanced Engineering and Science (IAES), 2019)
A design approach for a microstrip patch antenna to achieve the reconfigurable dual-band operation with a tunable device is presented in this work. The approach uses a BB833 varactor diode in the middle of a slotted patch antenna which which is able to produce dual-band resonant frequencies. The reconfigurable antenna is designed and simulated in CST Microwave Studio® software and is later, fabricated on a FR-4 substrate with a dielectric constant, εr of 4.5, loss tangent, tan δ of 0.019 and thickness, h of 1.6 mm. By changing the DC voltages of the varactor diode, different capacitance values of the varactor diode are obtained which dictate the specific resonant frequencies. From the simulation results, the capacitance value of 0.5 pF with a bias voltage of 2.0 V is chosen as it produces the required dual-band resonant frequencies at 3.38 GHz and 5.37 GHz for desired applications in the m-WiMAX and WLAN bands.